Eighteenth-century periodicals as agents of change perspectives on northern enlightenment - Krefting, Ellen M.; Nding, Aina; Ringvej, Mona Renate 1970- (Brill, 2015)
"Periodicals were an essential medium during eighteenth-century Enlightenment. The era's growing number of newspapers and journals made possible a fast and vast dissemination of ideas and debates. Journals were a particularly important means of transmitting ideas, genres, texts, and pieces of information from country to country, from centre to periphery, and from press to subscribers. These journals became agents of change by mediating the increasingly profound and widespread urge to write and read and to engage in political debate. This volume, edited by Ellen Krefting, Aina Nding and Mona Ringvej, presents contributions that explore this media revolution from a Northern perspective. The chapters throw new light on the reception of Enlightenment ideas and practices in Denmark-Norway, Sweden-Finland, and beyond. Taken together, they make a strong case for the transnational and revolutionary character of the Enlightenment as a whole"--
Papers originally presented at the conference "Periodical transfers: Eighteenth Century Journals as Agents of Change," held at Bogstad Manor outside Oslo in June 2013
Description based on print version record
Keywords: Periodicals -- History -- 18th century -- Congresses; Enlightenment -- Scandinavia -- Congresses; Social change -- Scandinavia -- History -- 18th century -- Congresses